STUDY ON FREQUENCY OF MUTATIONS FOR HVII REGION OF MITOCHONDRIAL DNA OF VIETNAMESE POPULATION SAMPLES AND APPLICATIONS IN FORENSIC IDENTIFICATION - Nguyen Thi Ngoc Anh,; Do Thi Xao Mai,; Nguyen Tien Thanh,; Nguyen Thi Le Dan,; Pham Van Binh,; Nguyen Tien Tung, (Tạp chí Y học Quân sự, 2023)
There are many mutations in the hypervariable II region in mitochondrial DNA. Determining the frequency of mitochondrial HVII region mutations improves the reliability of identifying human remains using the mitochondrial DNA technique. Our study is mutations in the HVII region in mitochondrial DNA of 300 blood samples that were collected from 300 unrelated Vietnamese individual. Results: Determine 31 mutations in mitochondrial HVII region, in there, frequencies of 24 mutations are low 10% (77.41%), frequencies of mutations are 10-30% (16.14%), frequencies of 2 mutations are high 30% (6.45%).